Cytotoxic Triterpenoids from the Stembark of Aglaia argentea (Meliaceae) - Ace Tatang Hidayat; Kindi Farabi; Desi Harneti; Nurlelasari Nurlelasari; Rani Maharani; Ida Nurfarida; Unang Supratman; Yoshihito Shiono (Universitas Gadjah Mada, 2018)
Four dammarane-type triterpenoid compounds, dammar-24-en-3a-ol (1), 3-epi-cabraleahydroxy lactone (2), (E)-25-hydroperoxydammar-23-en-3b,20-diol (3), and dammar-24-en-3β,20-diol (4), were isolated from the methanolic extract of the stembark of Aglaia argentea. Compounds 1-4 were isolated for first time from this plant. The structure of isolated compounds were elucidated by spectroscopic methods including one and two-dimensional NMR as well as mass spectrometric analysis. Compounds, 1-4, along with a known synthetic analog, 20-hydroxy-dammar-24-en-3-on (5), were evaluated their cytotoxic activity against P-388 murine leukemia cells in vitro. The IC50 values of compounds, 1-5 were 9.09 ± 0.10, 68.53 ± 0.08, 5.89 ± 0.08, 22.40 ± 0.11, and 11.53 ± 0.08 µg/mL, respectively. Among the dammarane-type triterpenoids, compounds 1, 3, 4 and 5 having opened side chain showed the stronger activity, wheres compound 2 with cyclic side chain showed weak or no activity. In addition, compound 3 showed strongest activity, indicate that hydroperoxy group at side chain increase cytotoxic activity.